THE EFFECT OF PMDN AND SUKUK ON LABOR ABSORPTION THROUGH GRP IN MEDAN CITY - Hasibuan, Winda Khairani; Tambunan, Khairina; Harahap, Muhammad Ikhsan (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
The results of this study indicate that increases in domestic investment (PMDN) and the utilization of Sukuk play a significant role in driving labor absorption in Medan City, both partially and simultaneously. Specifically, PMDN has a significant effect on employment, with a t-value of 3.600 and a significance level of 0.001, while Sukuk also shows a meaningful partial influence, reflected by a t-value of 3.933 and a significance level of 0.000. Together, the combined effect of PMDN and Sukuk on employment is substantial, as evidenced by an F-value of 86.179, far exceeding the F-table reference of 3.35, accompanied by a significance level of 0.000. These findings indicate that strengthening domestic investment and optimizing Islamic financial instruments like Sukuk not only positively impact GRDP as an intervening variable but also directly enhance employment opportunities in Medan City.Keywords: Domestic Investment, Sukuk,Labor Absorption